REDUPLIKASI DALAM KUMPULAN CERPEN PILIHAN KOMPAS 2014 DI TUBUH TARRA, DALAM RAHIM POHON - Tini Tiana; Ahadi Sulissusiawan; Agus Syahrani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2017)
AbstractReduplication in a collection of Kompas Chosen Short Stories 2014 Di Tubuh Tarra, dalam Rahim Pohon.This research is focused on the field of morphology, which is reduplication in a collection of Kompas Chosen Short Stories 2014 Di Tubuh Tarra, dalam Rahim Pohon. The main problem is limited to two sub-problems concerning the description of the form and the meaning of reduplication.The method used in this research is study documenter method in qualitative form. The source of data in this research is the collection of Kompas Chosen Short Stories 2014 Di Tubuh Tarra, dalam Rahim Pohon. The date in this research are the observations on words which contain forms and meanings of reduplication.Based on the results of the data analysis, it is concluded that in a collection of Kompas Chosen Short Stories 2014, there are 134 words and 134 words denote the meaning of reduplication. Keywords: Reduplication, Collection Kompas Stories.